"Fallen down" = "broken down"? The influence of the parking status of dockless shared bikes on consumers' willingness to use. (June 2022) - Chen, Ming; Yu, Shih-Heng; Ding, Shaohua
Abstract: Bike share programs (BSPs), which are a form of public transportation service that makes bicycles available for shared use on a short-term basis, have developed dramatically. As a new mode of BSP, dockless shared bikes (DSBs) are receiving increasingly more attention. Unlike the existing research on DSBs which concentrates on demand forecasting, static and dynamic repositioning, and transportation planning optimization, the present research focuses on the parking status, which is a unique characteristic of DSBs that is not relevant for station-based shared bikes. The results of a field study and a laboratory study revealed that consumers would have higher (lower) willingness to use upright (fallen) DSBs since they would consider fallen status as a signal of high risk. The effect is so strong that it occurs even for DSBs that are picked up while being observed by the consumer. In addition, the joint effect of motor fluency is also discussed. Our findings contribute to the literature on DSBs, risk perception, and motor fluency and provide insights into understanding consumers' decision-making process in choosing DSBs, optimizing the system efficiently and accurately, saving unnecessary costs, and decreasing environmental impacts. Highlights: Effect of the parking status of DSBs on consumers' willingness to use Examine the mediator role of consumers' risk perceptions toward DSBs Seeing a DSB change from fallen to upright status does not affect the perceptions. This effect remains after excluding the influence of motor fluency.